2022
DOI: 10.1126/sciadv.abn2276
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the concept of peptide bond planarity in an iron-sulfur protein by neutron structure analysis

Abstract: The planarity of the peptide bond is important for the stability and structure formation of proteins. However, substantial distortion of peptide bonds has been reported in several high-resolution structures and computational analyses. To investigate the peptide bond planarity, including hydrogen atoms, we report a 1.2-Å resolution neutron structure of the oxidized form of high-potential iron-sulfur protein. This high-resolution neutron structure shows that the nucleus positions of the amide protons deviate fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Neutron crystallography that can visualize H atoms is an extremely useful technique for that purpose. Structural details of NH–S bonds with ligand atoms of metalloproteins have only recently started to be uncovered by neutron and sub-ångström resolution X-ray crystallography, whereas it is well-known that they control redox potentials. The presence of the NH–S bond at metal centers of various metalloproteins suggests that it is one of nature’s favorite strategies to tune the metalloprotein activity.…”
Section: Discussionmentioning
confidence: 99%
“…Neutron crystallography that can visualize H atoms is an extremely useful technique for that purpose. Structural details of NH–S bonds with ligand atoms of metalloproteins have only recently started to be uncovered by neutron and sub-ångström resolution X-ray crystallography, whereas it is well-known that they control redox potentials. The presence of the NH–S bond at metal centers of various metalloproteins suggests that it is one of nature’s favorite strategies to tune the metalloprotein activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hanazono et al (2022) reported the results of high‐resolution neutron crystallography. They obtained non‐hydrogen atom coordinates from 0.66 Å resolution x‐ray data of a high‐potential iron–sulfur protein and introduced them to the 1.2 Å resolution neutron crystallography to optimize the hydrogen positions (HiPIP; PDB http://firstglance.jmol.org/fg.htm?mol=7VOS).…”
Section: Discussionmentioning
confidence: 99%
“… Electron and nuclear density of HiPIP [ 13 ]. (A) Electron and nuclear density maps around the peptide bond between Pro12 and Thr13, and between Asn70 and Val71.…”
Section: Figurementioning
confidence: 99%
“…We have previously published our works on the X-ray crystal structures of both the reduced (~0.48 Å resolution) and oxidized (~0.80 Å resolution) states of HiPIP derived from a thermophilic purple bacterium, Thermochromatium tepidum [7][8][9][10][11][12]. Recently, we have collected neutron diffraction data at 1.2 Å resolution and X-ray diffraction data at 0.66 Å resolution for the oxidized state of HiPIP from T. tepidum, substantially high resolutions for protein structural research [13][14][15]. Generally, the coordinates of hydrogen atoms are constrained to ensure that the bond distances and angles with the atoms to which they are bonded maintain ideal geometries.…”
Section: Introductionmentioning
confidence: 99%